Pedestrian Safety During Road Construction Works Along Federal Route (F050) - Zahrul Ar-Razi Kahar Muzafar; Ambak, Assoc. Prof. Ts. Dr. Kamarudin (Recent Trends in Civil Engineering and Built Environment, 2025)
This study assesses the low level of safety of Federal Route (F050) in the Parit Raja area, specifically within road construction zones for pedestrian road users. It addresses the research gap regarding pedestrian safety during road construction works by examining the level of safety of the road according to pedestrian road users, as well as their behaviors. The objectives include determining pedestrians’ perception towards facility safety, facility convenience, vehicle speed, and pedestrians’ behavior when using the road according to the perceived safety and convenience levels, with recommendations for improvement. Data gathered from a survey conducted digitally and distributed to 150 pedestrian road users in Parit Raja were analyzed using SPSS. The findings highlighted significant concerns and the need for improved safety measures to protect pedestrians, suggesting potential areas for further research and development in pedestrian safety protocols and construction practices.